2018
DOI: 10.3390/ma11071138
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Orthodontic Miniscrews: Bending and Maximum Load of Different Ti-6Al-4V Titanium and Stainless Steel Temporary Anchorage Devices (TADs)

Abstract: Temporary anchorage devices (TADs) have been introduced into orthodontic clinical practice in order to allow tooth movements while avoiding strain on adjacent teeth. Miniscrews are available in the market with different diameters and materials. Accordingly, the purpose of the present report was to measure and compare the forces to bend and fracture different mini implants. Ti-6Al-4V titanium and stainless steel TADs of different manufacturers (Spider ScrewHDC; Mini Implants–Leone; Benefit–Orteam; Storm–Kristal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 43 publications
1
17
0
3
Order By: Relevance
“…The lowest success rate found for SS MIs was 50%, 14 and the highest was 100%. 15 Regarding Animal study Carano et al (2005) In vitro study Chen et al (2018) In vitro study Gritsch et al 2013Animal study Khan et al (2016) No use of both types of mini-implants Kliauga et al 2010In vitro study Natarajan et al 2017Studies not related with the research objective Pan et al 2012In vitro study Scribante et al (2018) In vitro study Tseng et al 2016In vitro study Tseng et al 2017In vitro study Tseng et al 2017In vitro study titanium MIs, the lowest success rate found was 84.46%, 20 and the highest was 100%. 15 Only one study reported that titanium MIs showed higher success rates than SS MIs and that a higher implant failure was found in the upper jaw when compared with the lower jaw.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest success rate found for SS MIs was 50%, 14 and the highest was 100%. 15 Regarding Animal study Carano et al (2005) In vitro study Chen et al (2018) In vitro study Gritsch et al 2013Animal study Khan et al (2016) No use of both types of mini-implants Kliauga et al 2010In vitro study Natarajan et al 2017Studies not related with the research objective Pan et al 2012In vitro study Scribante et al (2018) In vitro study Tseng et al 2016In vitro study Tseng et al 2017In vitro study Tseng et al 2017In vitro study titanium MIs, the lowest success rate found was 84.46%, 20 and the highest was 100%. 15 Only one study reported that titanium MIs showed higher success rates than SS MIs and that a higher implant failure was found in the upper jaw when compared with the lower jaw.…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…26,28 SS MIs are also used in orthodontics and present great mechanical properties and better resistance to breakage and penetration capability. 9,10,26 Some in vitro and animal studies have shown that the two materials present similar results with respect to fracture strength and torsion, 29 mechanical stability, and histological responses. 8…”
Section: Discussionmentioning
confidence: 97%
“…Even after transverse expansion with a conventional removable expansion plate and pulling of the attached upper first incisors against it, the plate would not have provided support due to the beginning of tooth change in the second mixed dentition. Mini-screw-assisted palatal expanders are supported with titanium [ 13 ], stainless steel [ 14 ], or orthodontic miniscrews, like the used bone-borne apparatus (IGPD). In addition, anchoring by implants offers the advantage that neither the setting of the incisors nor the palatal expansion is dependent on the compliance of the young patient.…”
Section: Discussionmentioning
confidence: 99%
“…This concern is particularly important when planning miniscrew assisted palatal expanders or other miniscrew supported orthodontic devices with a completely digital workflow [ 32 ]. In these cases, the accuracy of the measurements is particularly important, thus allowing the clinician to choose diameter and type of miniscrew as these characteristics have a great influence on the mechanical behavior of the screws [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%